2022
DOI: 10.3389/fcomm.2021.796425
|View full text |Cite
|
Sign up to set email alerts
|

Discursive Power: Trade Over Health in CARICOM Food Labelling Policy

Abstract: Moving towards a more sustainable, healthier, and equitable food future requires a significant system transformation. Policies to achieve this transformation are notoriously difficult to achieve, especially where actors with conflicts of interest are involved in governance. In this paper, I analyze how corporate actors frame issues inside a process to develop Front-of-Pack Labelling across the Caribbean. Focusing on three major framing strategies, I show how industry actors argued 1) (falsely) that FOPL would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Articles on food, power, and health center their analysis on the economic and political power exercised by Big Food, which is the name given to the transnational corporations that drives the global consumption of unhealthy ultra-processed food and beverages (Baker et al 2021b). Market and political practices by Big Food serve to shape consump-tion patterns in the processes of food system transformations in developing countries (Baker and Friel 2016) and to influence policy and decision making in the field of food safety regulation (Clapp and Scrinis 2017;Hinton 2022;Miller and Harkins 2010). Big Food also enters trade disputes to reach their goals in battles around state discrepancies in the safety and acceptability of food standards and technological innovation (Quark 2016;Schram and Townsend 2020).…”
Section: The Relationship Between Food System and Healthmentioning
confidence: 99%
“…Articles on food, power, and health center their analysis on the economic and political power exercised by Big Food, which is the name given to the transnational corporations that drives the global consumption of unhealthy ultra-processed food and beverages (Baker et al 2021b). Market and political practices by Big Food serve to shape consump-tion patterns in the processes of food system transformations in developing countries (Baker and Friel 2016) and to influence policy and decision making in the field of food safety regulation (Clapp and Scrinis 2017;Hinton 2022;Miller and Harkins 2010). Big Food also enters trade disputes to reach their goals in battles around state discrepancies in the safety and acceptability of food standards and technological innovation (Quark 2016;Schram and Townsend 2020).…”
Section: The Relationship Between Food System and Healthmentioning
confidence: 99%
“…We supplement those with an in-depth thematic review of political actions and practices that have been or are being used to transform food systems. We approach this review from a holistic perspective, drawing on transformation-relevant processes rooted in the traditional political economy analysis of structural issues and power dynamics (IPES-Food, 2017;Leach et al, 2020), complemented by more sociological locations of politics/power as embedded in discursive practices (Hinton, 2022), technological innovations (Hutter and Lawrence, 2021), knowledge (Szanton, 2004), and consumption choices (Boström and Micheletti, 2019). As such, the review is non-exhaustive but thorough (1,011 documents identified through Web of Science and Google Scholar were initially reviewed after searching with keywords corresponding to the Framework's themes).…”
Section: Introductionmentioning
confidence: 99%